Ablation of AgRP neurons impairs adaption to restricted feeding - Keith Tan; Zachary A. Knight; Jeffrey M. Friedman (Elsevier, 2014)
While the SCN controls the circadian clock, further evidence suggests the existence of a food-entrainable oscillator (FEO) that links behavior to changes in food availability such as during restricted feeding (RF). We found that the activity of AgRP/NPY neurons changed rhythmically during RF suggesting that these neurons are a component of the FEO. We next ablated AgRP/NPY neurons in neonates with diphtheria toxin resulting in the loss of ∼50% of AgRP/NPY neurons. Body weight and food intake were unchanged in adult animals after neonatal ablation, as were the responses to leptin treatment, leptin withdrawal, food deprivation and ghrelin treatment. However, ablated animals showed 30% mortality within 4 days of RF. Moreover, the recovery of body weight and food intake in surviving animals lagged behind controls with an absence of food anticipatory activity even after three days. These findings identify AgRP/NPY neurons as a key cellular component of the food-entrained oscillator.